The Development of Smart Wheel Media For Reading Recognition to 1st Grade Students of MI Mamba'ul Huda - Fatimatuzzahro Fatimatuzzahro; Zumrotus Sa'diyah; Firda Zakiyatur Rofi'ah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2022)
The development of smart wheel media for early reading recognition is a relatively new thing. This is because the media will continue to grow and continue to be developed according to needs. Developing smart wheel learning media into a more feasible and effective media, 2. 1st-grade students' responses using smart wheel learning media for reading recognition to 1st-grade students of MI Mamba'ul Huda. This study uses the R&D (Research and Development) method, using the model developed by Borg and Gall. by designing media development. Data collection was carried out by means of observation, interviews, and documentation studies followed by a questionnaire. Data analysis techniques include validity testing by experts. The results showed that the media that the researchers had created was suitable for use in accordance with the validity test of material experts and learning media experts, based on media validation by smart wheel media expert got a percentage of 84% getting very good criteria, then based on material validation by reading learning materials experts the beginning of getting a percentage of 78% got good criteria, and the analysis of student responses to learning got a percentage of 96%.